Differential Exposure to Climate Change? Evidence from the 2021 Floods in Germany - Moritz Odersky; Max Löffler (Institute of Labor Economics (IZA), 2023)
We analyze the exposure of different income groups to the 2021 floods in Germany, which serve as an exemplary case of natural disasters intensified by anthropogenic climate change. To this end, we link official geo-coded satellite data on flood-affected buildings to neighborhood-level information on socio-economic status. We then document the empirical relationship between flood damages and household income. We limit comparisons to the vicinity of affected rivers and absorb a rich set of regional fixed effects to assess the differential exposure at the local level. Average household income is around 1,500 euros or three percent lower in flood-affected neighborhoods than in non-affected neighborhoods nearby. Our study is the first to document this regressive exposure along the income distribution based on actual flood damage data in Europe.
Keywords: Q52; Q54; D30; 330; climate change; differential exposure; floods; income distribution